2012
DOI: 10.1371/journal.ppat.1002860
|View full text |Cite
|
Sign up to set email alerts
|

Self-Enhancement of Hepatitis C Virus Replication by Promotion of Specific Sphingolipid Biosynthesis

Abstract: Lipids are key components in the viral life cycle that affect host-pathogen interactions. In this study, we investigated the effect of HCV infection on sphingolipid metabolism, especially on endogenous SM levels, and the relationship between HCV replication and endogenous SM molecular species. We demonstrated that HCV induces the expression of the genes (SGMS1 and 2) encoding human SM synthases 1 and 2. We observed associated increases of both total and individual sphingolipid molecular species, as assessed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 50 publications
5
69
0
Order By: Relevance
“…In fact, the results shown in the present report indicate that a higher content of cellular SM (ASMko mice, NPA fi broblasts, or addition of exogenous SM) promoted WNV infection. This effect of SM on WNV infection is also consistent with the recently reported positive effect of SM on hepatitis C virus replication ( 19,54 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In fact, the results shown in the present report indicate that a higher content of cellular SM (ASMko mice, NPA fi broblasts, or addition of exogenous SM) promoted WNV infection. This effect of SM on WNV infection is also consistent with the recently reported positive effect of SM on hepatitis C virus replication ( 19,54 ).…”
Section: Discussionsupporting
confidence: 91%
“…Lipidomic analyses have shown an increase in the content of both ceramide and SM in fl avivirusinfected cells ( 8,12 ), and ceramide has specifi cally been associated with WNV replication and viral particle biogenesis ( 8,9 ). Regarding SM, it is enriched in membranes from the replication complex of viruses phylogenetically related to WNV, such as dengue virus and hepatitis C virus ( 12,19 ). For WNV, an enrichment of SM in the viral envelope relative to total cellular membranes has been described ( 8 ).…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…HCV RNA replication is thought to occur in modified ER membranes condensed in the form of a membranous web (16). It has been shown that HCV replication occurs at specific ER locations within detergent-resistant membrane subdomains rich in cholesterol and specific subsets of sphingolipids (17)(18)(19)(20). While all the viral components of the replicase complex are directly or indirectly bound to the ER membrane, only NS4B (21) and NS5A (22) have been shown to be capable of modifying the architecture of the membranes where they are inserted, and this property is essential for efficient HCV RNA replication (21,22).…”
mentioning
confidence: 99%
“…While all the viral components of the replicase complex are directly or indirectly bound to the ER membrane, only NS4B (21) and NS5A (22) have been shown to be capable of modifying the architecture of the membranes where they are inserted, and this property is essential for efficient HCV RNA replication (21,22). Other viral proteins promote membrane remodeling by recruiting specific lipids (20) or cellular enzymes capable of producing a specific lipid environment (23,24). These modifications and others derived from the direct interac-tion of viral proteins with multiple cellular factors (25,26) lead to the construction of specialized structures that bear the viral replicase (22).…”
mentioning
confidence: 99%